2016
DOI: 10.1155/2016/8713037
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Treatment for Primary Septic Arthritis of the Hip in Adults

Abstract: Purpose. Primary septic arthritis is a rare differential diagnosis of acute hip pain in adults. Inspired by the success of all-arthroscopic treatment in pediatric patients, we developed a diagnostic and surgical pathway for our adult patients. Methods. Seven patients, average age 44 ± 13.7 years with acute hip pain since 4.4 ± 2.9 days in the average, were included. Septic arthritis was confirmed by joint aspiration and dissemination was excluded by MRI and standard radiographs. Surgical treatment consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 41 publications
(41 reference statements)
0
28
0
9
Order By: Relevance
“…Primary SA of the hip is rare in adults [13], which lead to serious complications and significant morbidity and mortality if it is not diagnosed and treated promptly [14] Two-step total hip arthroplasty has been used when the hip suffer from severe destruction [15]. In our study, we found that a main type of microorganism was Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 76%
“…Primary SA of the hip is rare in adults [13], which lead to serious complications and significant morbidity and mortality if it is not diagnosed and treated promptly [14] Two-step total hip arthroplasty has been used when the hip suffer from severe destruction [15]. In our study, we found that a main type of microorganism was Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 76%
“…Treatment of advanced knee arthritis in the setting of infection is a clinical challenge. The mainstays of treatment for infection in the nonarthritic knee (surgical debridement, lavage, and intravenous antibiotics) do not sufficiently address any resulting cartilage damage or deformity [ [22] , [23] , [24] ]. Although this situation is rare compared to the frequency of PJI, it is important to optimize treatment for these patients, as patients with a history of infection about the knee are often more likely to develop PJI after primary TKA, especially if infectious treatment history information is limited [ [7] , [8] , [9] , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary SA of the hip is rare in adults [13], which lead to serious complications and significant morbidity and mortality if it is not diagnosed and treated promptly [14]. Two-step total hip arthroplasty has been used when the hip suffer from severe destruction [15].…”
Section: Discussionmentioning
confidence: 99%